2018
DOI: 10.1002/anie.201804205
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Mediated Polymerization without External Deoxygenation or Oxygen Scavengers

Abstract: As a method for overcoming the challenge of rigorous deoxygenation in copper‐mediated controlled radical polymerization processes [e.g., atom‐transfer radical polymerization (ATRP)], reported here is a simple Cu0‐RDRP (RDRP=reversible deactivation radical polymerization) system in the absence of external additives (e.g., reducing agents, enzymes etc.). By simply adjusting the headspace of the reaction vessel, a wide range of monomers, namely acrylates, methacrylates, acrylamides, and styrene, can be polymerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 46 publications
5
93
0
1
Order By: Relevance
“…[5] Fori nstance,t he inhibition of radical polymerizations by oxygen necessitates its removal by physical processes,such as nitrogen purging, [6] or via chemical routes such as the trapping of photosensitized singlet oxygen. [8] More sophisticated systems utilizing enzymes [9] or dye/ ascorbic acid combinations, [10] convert molecular oxygen into hydrogen peroxide,w hich may be further used for radical production. [8] More sophisticated systems utilizing enzymes [9] or dye/ ascorbic acid combinations, [10] convert molecular oxygen into hydrogen peroxide,w hich may be further used for radical production.…”
mentioning
confidence: 99%
“…[5] Fori nstance,t he inhibition of radical polymerizations by oxygen necessitates its removal by physical processes,such as nitrogen purging, [6] or via chemical routes such as the trapping of photosensitized singlet oxygen. [8] More sophisticated systems utilizing enzymes [9] or dye/ ascorbic acid combinations, [10] convert molecular oxygen into hydrogen peroxide,w hich may be further used for radical production. [8] More sophisticated systems utilizing enzymes [9] or dye/ ascorbic acid combinations, [10] convert molecular oxygen into hydrogen peroxide,w hich may be further used for radical production.…”
mentioning
confidence: 99%
“…Previously, it was observed that the I eff values obtained for polymerizations under air were lower than the ones obtained under nitrogen atmosphere. This has also been observed by other authors when using Cu(0) as oxygen scavenger in DMSO, with results showing that initiator (EBiB) was also responsible for oxygen consumption . To better understand the behavior of the Na 2 S 2 O 4 ‐catalyzed SARA ATRP on this matter, several model experiments were conducted using a solution of MA, CuBr 2 , and Me 6 TREN in EtOH/H 2 O = 90/10 (v/v) and an optical sensor to monitor the dissolved oxygen concentration.…”
Section: Resultsmentioning
confidence: 72%
“…S1). The presence of unreacted chains, during copolymerization in the presence of air has been also observed in others studies reported in the literature . It is worth mentioning that none of the monomers added on steps 2 or 3 of chain extensions were previously degassed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, given the recent interest in oxygen-tolerant polymerisations, [39][40][41] we also wanted to perform an identical polymerisation in the absence of any external deoxygenation procedures while also using ppm levels of catalyst. Pleasingly, by decreasing the catalyst loading, broad and monomodal molecular weight distributions were obtained which further highlights the robustness of our approach ( Figure S11).…”
mentioning
confidence: 99%